# How to solve the expression where x = - x?

## Introduction to solving an equation with variables on both sides | Algebra I | Khan Academy

Last update: 2 answers

Previous questionWhy not locate crypto farms in the northern parts of the country? Isn't it easier to organize the cooling of video cards there? ?

Next questionWhat is the device in the photo?

### answers (2)

### Related question

## How to Find the Domain of Any Function (NancyPi)

## How to Factor Quadratic Expressions

## How To Evaluate Expressions With Variables Using Order of Operations

## Good afternoon. My account on mos.ru is doubled, how to solve the problem?

The account on mos.ru is doubled (the first one was created by state services - there is no security question, nothing), it is not possible to enter it, because when entering through public services, it sends to the second account, which states that the snls is involved in another account. When ...

## Answer 1

July, 2021move the -x from the right to the left of the equality. We get x - (- x) = 0 Open the brackets, minus by minus gives plus x + x = 0, we add 2x = 0, respectively, and we find x = 0/2, respectively, x = 0.

## Answer 2

July, 2021First, move the -x to the left of the expression. With this, we get: x - (- x) = 0. Next, you should open the brackets. Since minus by minus gives plus, it turns out x + x = 0. We carry out the addition, we get 2x = 0. The result is x = 0/2, where x = 0.